2014
DOI: 10.1002/nur.21581
|View full text |Cite
|
Sign up to set email alerts
|

Measuring African American Women's Trust in Provider During Pregnancy

Abstract: Significant racial disparities exist in pregnancy outcomes, but few researchers have examined the relationship between trust in providers and pregnancy outcomes. The Trust in Physician Scale (TPS), the most widely used tool, has not been tested in pregnancy. We assessed the psychometric properties of the TPS and identified correlates of trust in 189 pregnant African American women. Evidence supports internal consistency reliability (>.85) and internal structure of the TPS (CFI = .97; RMSEA = .05; χ(2) (42) = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…Previous literature identified two distinct gaps in care that had the potential for contributing to health disparity: structural variable and process variables (Peters, 2014). After the data were analyzed, the students were variables in both categories thus verifying and extending the findings of this previous study in profound ways that tied into the deeper historical context of the community and the mission of the medical school.…”
Section: Finding a Health Care Institutionsupporting
confidence: 75%
See 3 more Smart Citations
“…Previous literature identified two distinct gaps in care that had the potential for contributing to health disparity: structural variable and process variables (Peters, 2014). After the data were analyzed, the students were variables in both categories thus verifying and extending the findings of this previous study in profound ways that tied into the deeper historical context of the community and the mission of the medical school.…”
Section: Finding a Health Care Institutionsupporting
confidence: 75%
“…A study that surveyed African-American women reported that women's trust in their health care providers was related to the woman's history of perceived racism in the community (Peters, 2014). My study, thus, has verified findings that community matters and discrimination faced in a community is translated into perceptions of care and may impact birth outcomes.…”
Section: Seeking a Health Care Homesupporting
confidence: 64%
See 2 more Smart Citations
“…Typical prenatal care is rushed, brief, and focused on the health and development of the fetus, making it difficult to develop a trusting relationship. Trust is an important component of the patient- provider relationship, but has not been adequately studied in vulnerable populations (Peters, Benkert, Templin, & Cassidy-Bushrow, 2014). Determining how to interact with a healthcare provider to obtain optimal support has become a priority in rural health research (Price & Proctor, 2009).…”
Section: Introductionmentioning
confidence: 99%